Reconsidering dependence on life-sustaining treatment as a criterion for assisted suicide: the Italian legal unicum in comparative perspective - Albore, Marco; Sorace, Letizia; Del Prete, Sossio; La Russa, Raffaele; Volonnino, Gianpietro; Frati, Paola; Bolino, Giorgio (Frontiers in Public Health, 2025)
The legalization of Medical Assisted Voluntary Death, including assisted suicide is spreading worldwide, alongside the recognition of the centrality of the patient’s right to self-determination even in case of therapeutic desistance. In Italy Law-no. 219/2017 has granted patients the option of refusing therapy including life-sustaining treatments even without justification. The present paper offers a critical analysis of the legal-normative aspects and ethical-clinical implications of constraining assisted suicide to dependence on life-sustaining treatments. Reviewing some of the key bioethical-legal pronouncements, we discuss the current Italian system on assisted suicide in which dependence on life-sustaining treatment, even after the recent Constitutional sentences, is still one of the mandatory requirements, despite several critical profiles. Through a literature overview on medical life-sustaining treatments notion, the dependence on them is analyzed and assessed in clinical, bioethical and validity terms as a requirement for access to assisted suicide. From this it appears how dependence on life-sustaining treatment constraint shows overly ambiguous definitional boundaries, with the risk of inhomogeneous interpretations especially in the Italian framework. Interestingly, our comparative analysis reveals that Italy is a global legal unicum among the main international systems regulating Medical Assisted Voluntary Death; which, conversely, tend to target the issue on terminally or irreversibly suffering patients, independently of dependence on life-sustaining treatment.